2009
DOI: 10.1111/j.1748-1716.2008.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of herring (Clupea harengus) and herring fractions on metabolic status in rats fed a high energy diet

Abstract: The results suggest that addition of herring or herring oil counteracts negative effects on blood lipids induced by a high energy diet. The lipid component of herring thus seems to be responsible for these beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The dominant fatty acids in herring, namely the MUFA GA and CA, could not be detected in plasma after the herring meals (Table 3). This is in line with results obtained in an animal study, where only low amounts of GA and no CA was detected in plasma of rats consuming a herring diet for 6 weeks [51].…”
Section: Discussionsupporting
confidence: 94%
“…The dominant fatty acids in herring, namely the MUFA GA and CA, could not be detected in plasma after the herring meals (Table 3). This is in line with results obtained in an animal study, where only low amounts of GA and no CA was detected in plasma of rats consuming a herring diet for 6 weeks [51].…”
Section: Discussionsupporting
confidence: 94%
“…This fatty acid is also found in high amounts in herring [70,71], capelin and sand eels [72]. A herring diet and herring oil counteracted the negative metabolic effects in rats induced by a high-fat, high-sugar diet, probably due to the lipid composition being rich in EPA, DHA, cetoleic acid and gadoleic acid (20:1n-11) [71]. A recent study found that supplementation with saury oil, a fish oil high in gadoleic acid and cetoleic acid, improved plasma lipids in healthy subjects, indicating that there are other nutritional components besides EPA and DHA in fish which are important for cardiovascular health [73].…”
Section: Discussionmentioning
confidence: 86%
“…The amount of monounsaturated fatty acids was high in the lantern fish species (Table 5), of which cetoleic acid (22:1n-11) was especially high. This fatty acid is also found in high amounts in herring [70,71], capelin and sand eels [72]. A herring diet and herring oil counteracted the negative metabolic effects in rats induced by a high-fat, high-sugar diet, probably due to the lipid composition being rich in EPA, DHA, cetoleic acid and gadoleic acid (20:1n-11) [71].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that herring or herring oil counteracts negative effects on blood lipids and reduces atherosclerosis induced by a high‐energy diet in rats and that the lipid component of herring seems to be responsible for these beneficial effects (Lindqvist et al . , Gabrielsson et al . ).…”
Section: Discussionmentioning
confidence: 99%